2022
DOI: 10.3926/jotse.1583
|View full text |Cite
|
Sign up to set email alerts
|

The impact of research-oriented collaborative inquiry learning on pre-service teachers' scientific process skills and scientific attitudes

Abstract: In the past decade, scientific process skills and scientific attitudes are widely regarded as essential factors influencing students’ achievement and their future career choices. Unfortunately, previous literature found that students’ scientific skills and attitudes tend to be unsatisfactory. Thus, cultivating students’ skills and attitudes is seen as a fundamental goal in science education. This research sought to promote scientific process skills and scientific attitudes of pre-service chemistry teachers usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Some research has shown that REORCILEA is effective in increasing students' attitudes. In this model, students are required to develop ideas through several scientific steps such as promoting ideas, asking questions, explaining phenomena, and connecting learning (Irwanto, 2022). The effectiveness of the REORCILEA towards scientific attitudes is evidenced by previous studies such as the student who applies REORCILEA in learning had a high score for scientific attitude, so REORCILEA effectively improve students' scientific attitude (Huda and Rohaeti, 2021).…”
Section: Results Of Instructional Methods Themementioning
confidence: 99%
“…Some research has shown that REORCILEA is effective in increasing students' attitudes. In this model, students are required to develop ideas through several scientific steps such as promoting ideas, asking questions, explaining phenomena, and connecting learning (Irwanto, 2022). The effectiveness of the REORCILEA towards scientific attitudes is evidenced by previous studies such as the student who applies REORCILEA in learning had a high score for scientific attitude, so REORCILEA effectively improve students' scientific attitude (Huda and Rohaeti, 2021).…”
Section: Results Of Instructional Methods Themementioning
confidence: 99%
“…Computer-based learning media can be used to improve students' academic achievement [77]. Meanwhile, online laboratory learning also enhances academic achievement [78], [79], [80]. Furthermore, blended learning, the use of science experiments and the use of technology that assists learning can also increase students' academic achievement [81], [82].…”
Section: Academic Achievementmentioning
confidence: 99%
“…The Youth Scientific Group (YSG) is a form of extracurricular activity that provides benefits to high school students. Through YSG activities, students are introduced to the scientific method, enabling them to learn research skills and enhance their scientific competence (Duc et al, 2022;Irwanto, 2022;Yeoman & Zamorski, 2008). With YSG activities that involve training students in writing research papers, their literacy and writing skills will also be empowered (Prahmana, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With YSG activities that involve training students in writing research papers, their literacy and writing skills will also be empowered (Prahmana, 2017). In line with these benefits, their scientific attitude will also improve as they gain more research experience (Irwanto, 2022). Additionally, the opportunity to participate in YSG competitions will provide them with competitive experiences and prepare them to compete at higher levels of education.…”
Section: Introductionmentioning
confidence: 99%